Polymer-supported nanomaterials for photodegradation: Unraveling the methylene blue menace - Sadia Muzammal; Awais Ahmad; Mahshab Sheraz; Juran Kim; Shafaqat Ali; Muhammad Bilal Hanif; Iftikhar Hussain; Saravanan Pandiaraj; Abdullah Alodhayb; Muhammad Sufyan Javed; Hussein A.Z. Al-bonsrulah; Martin Motola (Energy Conversion and Management: X, 2024)
In the modern era, the inaccessibility of safe drinking water has become a hot issue. In this regard, industrial chemicals are one of the most well known pollutants that disturb the water quality and make it flabby for comsumption. Amongst these pollutants, methylene blue is the most noxious, persistent, and oncogenic, as well as posing a severe risk to human health and environmental protection. This is frequently found in natural reserviors, which turn out to be a health hazard to human beings and other organisms. So, it is necessary to introduce efficient and eco-friendly techniques for eliminating organic dyes from wastewater. To meet this goal, photodegradation of the pollutants has been one of the most efficient and reliable approach for the removal of organic dyes. It can completely mineralize the dyes into nontoxic species in a cost-effective way. This article helps readers who are interested in exploring their expertise in this research area. In our study, we address both the fundamental principles of photodegradation and explore the application of polymer-supported nanomaterials for organic pollutant degradation. Our study has addressed critical parameters like irradiation time, oxidants, scavengers, pH, catalyst dosages, and most importantly, the role of reactive oxygen species in the degradation of organic dyes. This article provides a concise overview of the principles of photocatalysis, including mechanisms, reaction schemes, and end products of dye degradation. It also discusses the future outlook for consuming dyes on an industrial scale. Additionally, the article categorizes the approaches for developing efficient photocatalytic degradation of dyes.